Sketsa Dakwah Islam di Eropa Barat - Aliyudin, Aliyudin (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2015)
The history of DakwahÂ in West-EropaÂ can be devided in two patterns: The first, from century 8th to 15th , named at least as politic dakwah. Muslims have real authority in some areas: a few islands in midle sea and minor place in south-Italia and Franch, nor Spanish and Sicilia. The second, sine 19th centuryÂ till now, muslims havenâ€™t political authority. The pattern of dakwah only depend on profile, personality, performance of muslim imigransÂ behavior as worker, trader, student, diplomat, ect.